2006
DOI: 10.1111/j.1365-2672.2006.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a bacterial strain of the genus Ochrobactrum with methyl parathion mineralizing activity

Abstract: Aims:  To isolate and characterize a methyl parathion (MP)‐mineralizing bacterium, and to elucidate the degradative pathway of MP and localize the responsible degrading genes. Methods and Results:  A bacterial strain, designated B2, capable of mineralizing MP was isolated from the MP‐polluted soil. Analysis of the 16S rRNA gene sequence and phenotypic analysis suggested that strain B2 had a close relationship with Ochrobactrum anthropi. B2 could totally degrade MP and four metabolites [p‐nitrophenol (PNP), 4‐n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Studies on pure cultures of Rhizobiales have shown that they may also be capable of degrading methyl parathion, metolachlor, polyacrylamides, and quaternary ammonium alcohols, all potential source water contaminants (14,23,27,39).…”
mentioning
confidence: 99%
“…Studies on pure cultures of Rhizobiales have shown that they may also be capable of degrading methyl parathion, metolachlor, polyacrylamides, and quaternary ammonium alcohols, all potential source water contaminants (14,23,27,39).…”
mentioning
confidence: 99%
“…All cultures were grown with shaking at 30°C. At each time point, a 1 mL aliquot was withdrawn and centrifuged, and the supernatant was stored at -20°C for PNP analysis by HPLC (28). (Figure 1).…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…PNP and its metabolites were determined using an Agilent 1100 series HPLC equipped with a diode array detector (DAD) and a Zorbax 300SB-C18 column. Details for GC and HPLC analyses are described by Qiu et al (27). The pH was determined using a digital pH meter (PH-3C, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrite ion was quantitatively determined by the method of Montgomery and Dymock (26). PNP was quantified by HPLC (Agilent 1100), and its metabolites were identified by GC-MS (6890N GC-5973N MSD, Agilent Technologies, Palo Alto, CA) (27). Hydroquinone oxidation was monitored spectrophotometrically by measuring the increase at 320 nm (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation